Science and Civilisation in China. Vol. 1 Introductory Orientations - and Needham, Joseph (Cambridge University Press, 1956)
Dr Joseph Needham's account of the Chinese achievement in science and technology will stand as one of the great works of our time. It has been acclaimed by specialists in both East and West and also by readers with wider and more general interests. The text, based on research of a high critical quality, is supported by many hundreds of illustrations and is imbued with a warm appreciation of China. Volume I is an introductory volume, in which Dr Needham prepares his readers for the study of a whole human culture. He begins by examining the structure of the Chinese language; he reviews the geography of China and the long history of its people, and discusses the scientific contacts which have occurred throughout the centuries, between Europe and East Asia.